Biophysics week in Ukraine: online meeting of the Kharkiv branch of the Ukrainian biophysical society - Berest, V. P.; Gorobchenko, O. A. (Biophysical Bulletin, 2025)
As part of Biophysics Week 2025, V. N. Karazin Kharkiv National University on March 24 hosted the event “Biophysics Week in Ukraine: Experience Across the Borders”, bringing together researchers, students, and professionals to highlight the latest advancements in biophysics. This event served as a platform for sharing experiences, expertise and forecasts between Ukrainian biophysicists working at home and abroad, discussing cutting-edge research, fostering collaboration, and promoting the role of biophysics in addressing global scientific and educational challenges.